Perpaduan Sistem Kontrol Berbasis IoT Pada Hidroponik NFT Untuk Pemantauan Dan Pengendalian Nutrisi Pada Budidaya Anggrek Akar Angin Orchids Di Kabupaten Kediri - Dani Irawan; Erwin Komara Mindarta; Grace Tjandra Leksana; Monika Dwi Laily; Erdiano Adila Suryadinata (CV. Multi Kreasi Media, 2023)
The objectives of this community service activity are (1) Producing appropriate technology in the form of an IoT -Based Control System for NFT Hydroponics for monitoring and Controlling Nutrition in Orchid Cultivation for service partners, (2) Conducting technical guidance on the use of IoT -Based Control System tools for NFT Hydroponics for Monitoring and Control of Nutrition in Orchid Cultivation to produce superior and quality orchid seeds, (3) Providing assistance on how to process AB MIX organic liquid fertilizer which is then integrated into the NFT hydroponic system. The method used in this community service activity is community empowerment through training and mentoring. The results of the Workshop on agricultural automation systems for farmer groups in Kediri Regency are one of the efforts made to improve economic recovery, especially to increase the quality and quantity of agricultural products. In this community service activity it is also hoped that it will be able to build the competency of the farming automation system in farmer groups in Kediri Regency. This activity can bring farmer groups who still use conventional methods to modern ways by implementing monitoring and automation systems.